Taxonomic notes on the antlion tribe Palparini Banks (Neuroptera: Myrmeleontidae) from Pakistan - Hassan, Muhammad Asghar; Akhtar, Saleem; Zheng, Yuchen; Liu, Xingyue (Zootaxa, 2023)
The antlion tribe Palparini Banks, 1911 (Myrmeleontidae: Ascalaphinae) currently comprises five genera and seven species in Pakistan. The taxonomic status of three genera, namely Indopalpares Insom & Carfi, 1988, Palpares Rambur, 1842, and Parapalpares Insom & Carfi, 1988, are revised herein. Indopalpares pardus (Rambur, 1842), Palpares zebratus Rambur, 1842, and Parapalpares solidus (Gerstaecker, 1894) are redescribed based on the material from the northern areas of Pakistan. The following taxonomic and nomenclatural changes are proposed: Palpares patiens is re-established as valid species, and P. infimus is transferred to senior synonym of P. patiens from P. zebratus; Palpares trichogaster syn. nov. is considered a new synonym of Palpares zebratus. The re-find of the rarely known endemic species Palpares zebratus from northern areas in Pakistan reveals its wider distribution far from its type localities in the southern Indian state (Tamil Nadu) and the southern province in Pakistan (Sindh). Taxonomic remarks, distribution maps, and detailed photographs of three species are provided based on both external morphological and genital characters.